Educating the Global-Minded Business Professional and Manager (2020)
One of the main concerns in human resource management around the world is how education is encouraging the understanding of global issues, cultures, technological changes and social trends to make appropriate decisions in firm management. This chapter will aim to illustrate the main issues in international business (IB) theory and practice that need to be considered in configurating a global-minded curriculum that is able to produce global-minded human resources. Hence, to determine what inputs must be considered in building an exceptional curriculum and successful educational strategies, the author observe the assertions from three perspectives: first, the contributors to the IB and the multinational enterprise theory; second, the author explores the stakeholders’ perspective, who see the benefits and assume the consequences of education in the field; and third, the author reviews the researchers who in recent years have studied the problems and trends of the discipline. © 2021 by Emerald Publishing Limited.